2021
DOI: 10.1007/s00455-021-10363-8
|View full text |Cite
|
Sign up to set email alerts
|

Early Post-operative Feeding: An Investigation of Early Functional Outcomes for Oral Cancer Patients Treated with Surgical Resection and Free Flap Reconstruction

Abstract: Traditionally patients can remain nil by mouth (NBM) for up to 12 days after oral tumour resection with free flap reconstruction to reduce the risk of flap dehiscence, poor healing and fistulae. The literature reports that patients could on average remain an inpatient for up to 20 days post-surgery. An evaluation of the impact of a defined early oral feeding protocol was undertaken investigating functional outcomes and complications rates. We prospectively reviewed tracheostomy use, length of hospital stay, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Brady et al [ 32 ] demonstrated that early oral feeding was associated with a significant reduction in the length of hospital stay, with a median length of 10 days in comparison to previous studies conducted at the same center where patients received delayed feeding and subsequently had a longer hospital stay, with a median length of 20 days. A recent study conducted by Le et al [ 25 ] produced similar findings; 415 patients were included, with 71 patients allocated to the early feeding group (< 5 days) and 344 patients allocated to the late feeding group (> 5 days).…”
Section: Discussionmentioning
confidence: 99%
“…Brady et al [ 32 ] demonstrated that early oral feeding was associated with a significant reduction in the length of hospital stay, with a median length of 10 days in comparison to previous studies conducted at the same center where patients received delayed feeding and subsequently had a longer hospital stay, with a median length of 20 days. A recent study conducted by Le et al [ 25 ] produced similar findings; 415 patients were included, with 71 patients allocated to the early feeding group (< 5 days) and 344 patients allocated to the late feeding group (> 5 days).…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation continues with surgical healing and introduction of appropriate exercises and compensatory strategies as agreed with surgical colleagues. Following surgery, the emergence of early post-operative feeding protocols 42 and the prevention of respiratory complications from aspiration are paramount with the use of compensatory swallow strategies and adherence to a strict oral care protocol. 43 Intensive SLT input in the weeks after surgery aims to optimise voice and swallow safety with biofeedback techniques using flexible nasendoscopy.…”
Section: Slt Interventions Following Surgical Interventionsmentioning
confidence: 99%
“…6 In order to prevent fistula formation, surgeons have traditionally waited 6-14 days prior to initiating oral feeding, as it has been conceptualized that overuse of the oral mechanism in the early post-operative phase places excessive stress on the interface between the flap and oral mucosa. 7,8 While common practice, there is surprisingly little evidence for this in the literature, with its origination commonly traced to a pair of trials produced in the 1970s that each displayed higher rates of pharyngocutaneous fistula formation for patients beginning oral intake within the first 3 weeks following total laryngectomy. 9 Evolving knowledge of oral wound healing has called this conceptualization into question, as it has been shown that only marginal increases in wound strength occur between post-operative day 1 and the end of the traditional "nothing by mouth" period at post-operative day 14.…”
Section: Introductionmentioning
confidence: 99%
“…Common recipient site complications include microvascular thrombosis, flap failure, hematoma formation, wound dehiscence, salivary leak, and development of orocutaneous fistula 6 . In order to prevent fistula formation, surgeons have traditionally waited 6–14 days prior to initiating oral feeding, as it has been conceptualized that overuse of the oral mechanism in the early post‐operative phase places excessive stress on the interface between the flap and oral mucosa 7,8 . While common practice, there is surprisingly little evidence for this in the literature, with its origination commonly traced to a pair of trials produced in the 1970s that each displayed higher rates of pharyngocutaneous fistula formation for patients beginning oral intake within the first 3 weeks following total laryngectomy 9 …”
Section: Introductionmentioning
confidence: 99%